PENGARUH SISTEM INFORMASI AKUNTANSI, SISTEM PENGENDALIAN INTERN, GOOD GOVERNMENT GOVERNANCE, BUDAYA ORGANISASI TERHADAP KINERJA PT. PLN PERSERO SUB RAYON WUA-WUA DAN BENUA BENUA - Wiranto, Riswan; Awaluddin, Ishak; Akib, Mulyati (JPEP (Jurnal Progres Ekonomi Pembangunan), 2019)
This study aims to determine and analyze the effect of accounting information systems, internal control systems, go od Goverment governance, organizational culture on the performance of PT PLN (Persero) Sub Rayon Wua-Wua and continents. Respondents in this study were all employees of PT PLN (Persero) Sub Rayon Wua-Wua and continents who had positions as Managers, Supervision, assistants, juniors, staff. The total respondents were 105 people. Analysis of the data used in this study is a multiple linear regression analysis technique that is processed through SPSS version 23 software.The results of this study indicate that the t value of accounting information system (X1) is 7.729 with a significance of 0,000 (tsig = 0,000 more keci than the value of Î± = 0.05 thus, accounting information system variables have a significant effect on company performance. Internal Control System Variables (X2) of 2,244 with a significance level of 0,027 (tsig = 0,000) Smaller than the value of Î± = 0,05, the internal control system variable has a significant effect on company performance. Good Corporate Governance (X3) of 2,241 with significant 0,027 (tsig = 0,000 ) smaller than Î± = 0.05 05, the Good Governacne variable has a significant effect on company performance. Organizational Culture variable is 6.423 with a significance level of 0.000 (tsig = 0,000 smaller than the value of Î± = 0.05, the organizational culture variable has a significant effect on company performance. Â